A systematic investigation of drilling fluid bulk relaxation impact on NMR interpretation for formation evaluation - Fauzan Akomolafe; Ammar El-Husseiny; Abdulrauf Adebayo; Mohamed Mahmoud; Badr Bageri (Petroleum, 2025)
During drilling, mud filtrate invasion alters near-wellbore properties which possibly impacts well logging measurements causing inaccuracies in formation evaluation. Given the shallow detection depth of nuclear magnetic resonance (NMR) logging, the transverse relaxation time (T2) spectrum is highly susceptible to invasion effects. However, the impact of drilling fluid bulk relaxation on NMR T2 and formation damage remains underexplored. This study aims to investigate how drilling fluid bulk relaxation influences NMR T2 relaxometry responses in the near-wellbore region. Two factors controlling the drilling fluid bulk relaxation were considered and systematically varied: (1) XC polymer concentrations and (2) perlite concentrations in the drilling fluid. We conducted NMR measurements before and after filtration experiments on both permeable and tight limestone samples to assess the influence of host rock properties on the results. The study shows that drilling fluid bulk relaxation significantly impacts T2 values. Additives like XC polymer or barite lower T2 bulk values, reducing the T2 logarithmic mean by up to 90% especially in invaded macropores. The more notable impact in macropores is because they are more influenced by bulk relaxation mechanism compared to micropores. Rocks with larger pores experience greater reduction in T2, while tight rocks, dominated by surface relaxation, show mineral changes. The findings underscore the importance of accounting for drilling fluid bulk relaxation in NMR interpretation to avoid overestimating formation damage and permeability reduction.